The Relationship Between Coping and Quality of Life in Breast Cancer Patients - Roslima SNA, Ratu Syahdatul; Maryuni, Sri; Prayetni, Prayetni (Inspirasi Foundation, 2026)
Introduction: Breast cancer is the most common cancer among women and continues to increase globally, including in Indonesia. Patients undergoing chemotherapy often experience physical and psychological distress that may affect their quality of life. Coping mechanisms play an important role in helping patients adapt to these challenges, making it necessary to examine their relationship with quality of life in breast cancer patients. Objective: The aim of this study was to determine the relationship between coping mechanisms and the quality of life of breast cancer patients at RSUD Dr. H. Abdul Moeloek Lampung Province in 2024. Method: This research method uses a cross sectional design using the chi square sampling technique, totaling 82 respondents. This research instrument uses a questionnaire sheet on coping mechanisms and the quality of life of breast cancer patients Result: The research results showed that of the 82 respondents, 56 respondents (68.3%) had adaptive coping mechanisms and 26 respondents (31.7%) had maladaptive coping mechanisms. Meanwhile, of the 82 respondents who had a good quality of life, 55 respondents (67.1%), and 27 respondents (32.9%) had a poor quality of life. Conclusion: Based on the results of statistical tests, a p-value of 0.025 (p-value ≤ 0.005) was obtained, which means there is a relationship between coping mechanisms and the quality of life of breast cancer patients at RSUD Dr. H. Abdul Moeloek Lampung Province. It is hoped that the family will motivate and provide family support to the patient in healing and improving the patient's quality of life.